Are We Aware of What Is Going on in a Student's Mind? Understanding Wrong Answers about Plant Tropisms and Connection between Student's Conceptions and Metacognition in Teacher and Learner Minds - Ewa Sobieszczuk-Nowicka; Eliza Rybska; Joanna Jarmużek; Małgorzata Adamiec; Zofia Chyleńska (MDPI AG, 2018)
Problems with understanding concepts and mechanisms connected to plant movements have been diagnosed among biology students. Alternative conceptions in understanding these phenomena are marginally studied. The diagnosis was based on a sample survey of university students and their lecturers, which was quantitatively and qualitatively exploratory in nature (via a questionnaire). The research was performed in two stages, before and after the lectures and laboratory on plant movements. We diagnosed eight alternative conceptions before the academic training started. After the classes, most were not been verified, and in addition, 12 new conceptions were diagnosed. Additionally, we report that teachers are not aware of students’ possible misunderstandings. They do not perceive students’ troubles with switching between levels of representations, nor their alternative conceptions. A case of “curse of knowledge” was observed and academic teacher training is recommended. Additionally, the need for metacognition as a crucial element in laboratory activities seems supported by our presented results. Such metacognition refers to students as well as teachers, which leads to the conclusion that teachers should be aware of students’ way of thinking and the development of knowledge in one’s own mind.